A cell‐free testing platform to screen chemicals of potential neurotoxic concern across twenty vertebrate species. (26th July 2017) - Arini, Adeline; Mittal, Krittika; Dornbos, Peter; Head, Jessica; Rutkiewicz, Jennifer; Basu, Niladri
Abstract: There is global demand for new in vitro testing tools for ecological risk assessment. The objective of the present study was to apply a set of cell‐free neurochemical assays to screen many chemicals across many species in a relatively high‐throughput manner. The platform assessed 7 receptors and enzymes that mediate neurotransmission of γ‐aminobutyric acid, dopamine, glutamate, and acetylcholine. Each assay was optimized to work across 20 vertebrate species (5 fish, 5 birds, 7 mammalian wildlife, 3 biomedical species including humans). We tested the screening assay platform against 80 chemicals (23 pharmaceuticals and personal care products, 20 metal[loid]s, 22 polycyclic aromatic hydrocarbons and halogenated organic compounds, 15 pesticides). In total, 10 800 species–chemical–assay combinations were tested, and significant differences were found in 4041 cases. All 7 assays were significantly affected by at least one chemical in each species tested. Among the 80 chemicals tested, nearly all resulted in a significant impact on at least one species and one assay. The 5 most active chemicals were prochloraz, HgCl2, Sn, benzo[ a ]pyrene, and vinclozolin. Clustering analyses revealed groupings according to chemicals, species, and chemical–assay combinations. The results show that cell‐free assays can screen a large number of samples in a short period of time in a cost‐effective manner in a range of animals not easily studied using traditional approaches. Strengths and limitations of this approach are discussed, as well as next steps. Environ Toxicol Chem 2017;36:3081–3090. © 2017 SETAC